Contagious Animosity in the Field: Evidence from the Federal Criminal Justice System - McConnell, Brendon; Rasul, Imran (Journal of Labor Economics, 2021)
We investigate whether increased animosity toward Muslims after 9/11 had spillover effects on Black and Hispanic individuals in the federal criminal justice system. Using linked administrative data tracking defendants from arrest through sentencing, we find that after 9/11, sentence and presentence outcomes for Hispanic defendants significantly worsened. Outcomes for Black defendants were unchanged. The findings are consistent with judges and prosecutors displaying social preferences characterized by contagious animosity from Muslims to Hispanics. Our findings provide among the first field evidence of contagious animosity, indicating that social preferences across out-groups are interlinked and malleable.